HEARING A CASE IN COURT IN MEDIATION ORDER - Sharipov Asror Safar ugli (Journals Park Publishing, 2024)
This article examines the norms of collisions and measures to eliminate them in our national legislation.
Keywords: normative legal act, collision in law, legal norm, citizenship law, defect.